Effects of the outbreak of COVID-19 on oral health-care workers (HCWs) at the regional dental center in Qassim, Saudi Arabia - Wesam Talal Alsalman; Saad Mulhi Alharbi; Abeer Hani Albattah; Khalid Almas (Wolters Kluwer Medknow Publications, 2021)
Introduction: Since the emergence of the 2019 novel coronavirus (COVID-19), the pandemic has rapidly spread all over the globe, affecting millions of people and resulted in over 1,900,000 deaths. During the outbreak of COVID-19 situation, health-care workers in general and dental team specifically are at risk of developing psychological distress and other mental health symptoms. Aim: The study was conducted to investigate the effects of outbreak of coronavirus (COVID-19) on oral health-care workers (HCWs) at the Regional Dental Center in Qassim and how it affects their practice and daily life in terms of psychological, mental, behavioral manner, and social well-being. Materials and Methods: This is a cross-sectional, single dental care facility-based study. A bilingual questionnaire was distributed to a convenience sample of 150 HCWs. The questionnaire contained 26 questions covering the following domains: (a) demographic data, (b) knowledge testing and sources of information, (c) personal precautions and infection control measures, and (d) behavioral and psychological aspects. The questionnaire was distributed through the social media platform. Data were analyzed using SPSS version 22. Descriptive statistics were used for data summarization and presentation. Results and discussion: The response rate was 72% , with the age range from 18 to 54 years, with female 60% to male 40% distribution. A very high level of awareness about the COVID-19 ranging from 60% to 100% was found among participants. The main sources of information regarding coronavirus were Ministry of Health (MoH), social media, followed by the World Health Organization website. Almost 90% started regular hand hygiene and paying attention to the proper use of personal protective equipment. Almost 70% agreed to stop treating patients due to their perception of the risk of contamination. Almost 90% of them felt afraid of transferring the infection to their families. Majority of them spent their time on social media, while nearly 50% on reading and sleeping. Almost two-third of the participants do highly trust the precautions which have been taken by the MoH and the Regional Dental Center in Qassim. Conclusions: It is concluded that the HCWs had good knowledge and awareness about COVID-19. They are concerned about their safety and possibility of spread of infection to their families and considered to stop regular dental treatment. Their satisfaction is moderate about the safety measures provided by MoH and the center. Future research should be carried out at multicenter, primary, secondary, and tertiary care centers to generalize the findings.